Extracellular vesicles shuttle protective messages against heat stress in bovine granulosa cells - Gebremedhn, Samuel; Gad, Ahmed; Aglan, Hoda Samir; Laurincik, Jozef; Prochazka, Radek; Salilew-Wondim, Dessie; Hoelker, Michael; Schellander, Karl; Tesfaye, Dawit (Scientific reports, 2020)
Elevated summer temperature is reported to be the leading cause of stress in dairy and beef cows, which negatively affects various reproductive functions. Follicular cells respond to heat stress (HS) by activating the expression of heat shock family proteins (HSPs) and other antioxidants. HS is reported to negatively affect the bi-directional communication between the follicular cells and the oocyte, which is partly mediated by follicular fluid extracellular vesicles (EVs) released from surrounding cells. As carriers of bioactive molecules (DNA, RNA, protein, and lipids), the involvement of EVs in mediating the stress response in follicular cells is not fully understood. Here we used an in vitro model to decipher the cellular and EV-coupled miRNAs of bovine granulosa cells in response to HS. Moreover, the protective role of stress-related EVs against subsequent HS was assessed. For this, bovine granulosa cells from smaller follicles were cultured in vitro and after sub-confluency, cells were either kept at 37 °C or subjected to HS (42 °C). Results showed that granulosa cells exposed to HS increased the accumulation of ROS, total oxidized protein, apoptosis, and the expression of HSPs and antioxidants, while the viability of cells was reduced. Moreover, 14 and 6 miRNAs were differentially expressed in heat-stressed granulosa cells and the corresponding EVs, respectively. Supplementation of stress-related EVs in cultured granulosa cells has induced adaptive response to subsequent HS. However, this potential was not pronounced when the cells were kept under 37 °C. Taking together, EVs generated from granulosa cells exposed to HS has the potential to shuttle bioactive molecules to recipient cells and make them robust to subsequent HS.
Keywords: Cattle; Animals; skot; poruchy vyvolané tepelným stresem; apoptóza; Heat-Shock Response; Female; Apoptosis; ženské pohlaví; folikulární buňky; ovariální folikul; extracelulární vezikuly; stanovení celkové genové exprese; regulace genové exprese; nemoci skotu; Cattle Diseases; Extracellular Vesicles; reakce na tepelný šok; Gene Expression Regulation; zvířata; Ovarian Follicle; Heat Stress Disorders; Gene Expression Profiling; Granulosa Cells